Theoretical and Practical Aspects Regarding the Secrecy of Correspondence in Light of ECHR Jurisprudence - MOROȘTEȘ, Anca Florina; STOICU, Narcisa Mihaela (Journal of Legal Studies, 2014)
The rights, freedoms and duties of man are fundamental, par excellence, in an institution of constitutional law and, as such, quite naturally, they are contained in the body of the Constitution. Article 8 para. 1 of the European Convention on Human Rights refers to the right of every person to respect for his private life and family life, his home and his correspondence. This text corresponds to art. 12 of the Universal Declaration of Human Rights, which stipulates that no one shall be subjected to arbitrary interference with his privacy, family, home or correspondence, nor to attacks upon his honor and reputation. Also, art. 8 para. 1 of the Convention proclaims the right to communicate thoughts and opinions by writing, by telephone or two-way transmission or by any other means of communication, without being known to others, blacked out or made public. Accordingly, article 8 protects all types of correspondence, including communication by electronic means. This right is guaranteed and protected by art. 17 of the International Covenant on Civil and Political Rights.